Elevation and variability of acidic sandy soil pH: amended with conditioner, activator, organic and inorganic fertilizers - Basri, Mohd Hadi Akbar; Junejo, Nasima; Abdu, Arifin; Abdul Hamid, Hazandy; Kusno, Mohd Ashadie (Academic Journals, 2013)
Availability of nutrients for plant uptake is directly related to soil pH and as an indicator of soil fertility status. Determination of effects of soil amendments on soil pH should be a necessary part of fertilizer and fertility research. A pot experiment was carried out to determine and compare the effects of biochar, chicken manure, urea and zeolite on soil pH variability and elevation in a sandy loam acidic soil. A modified method was used to determine the soil pH in the pots. Soil pH in pot was measured by a glass micro-electrode and spatial variability was interpolated and mapped by using geographic information system (GIS) + software. Kriged Maps clearly showed the presence of variability and elevation in pH within each treatment. Furthermore, the position of patches with maxima and minima values for pH changed between all treatments used in the experiment. The highest elevation was found in zeolite treated soil followed by urea and biochar. However, a significant decrease was measured in soil pH in chicken dung treated soil. These findings could be the first step towards temporal stability of the pattern of spatial distribution of soil pH affected by the soil amendments (biochar, urea, chicken manure and zeolite).